Comparing the sealing properties of mineral trioxide aggregate and an experimental ceramic based root end filling material in different environments - Seyed Mohsen Hasheminia; Sam Loriaei Nejad; Omid Dianat; Jalil Modaresi; Faranak Mahjour (Wolters Kluwer Medknow Publications, 2013)
Background: An apical seal is an important factor in achieving success in surgical endodontics. Aim: The purpose of this study was to compare the sealing properties of mineral trioxide aggregate (MTA) with a new ceramic based root end filling material (Cold Ceramic) in different environments. Materials and Methods: One hundred teeth were selected. The root canals were instrumented and obturated. Except for the apical 2 mm, the root surfaces were sealed. After root resection, 3 mm depth root-end cavities were prepared. For each material, roots were divided into 3 equal subgroups and the root-end filling was done in different environments (dry, saliva contaminated, blood contaminated). Five roots served as positive and 5 roots as negative controls. Samples were immersed in 2% methylene blue dye. Roots were sectioned longitudinally and examined under stereomicroscope to record the extension of dye penetration. Results: All experimental groups demonstrated dye penetration. The lowest linear leakage was seen in Cold Ceramic blood contaminated group while the highest leakage was observed in MTA blood contaminated group. The linear dye penetration of both MTA and Cold Ceramic (CC) groups did not show any significant differences among different environments. Also, the difference between MTA and CC was not significant in dry and saliva contaminated subgroups. Only the difference between dye penetration of MTA and CC in blood contaminated subgroups showed significant difference ( P = 0.008). Conclusion: The sealing property of this ceramic based root end filling material (Cold Ceramic) is better than MTA in blood contaminated condition and at least similar to MTA in other conditions.